Особливості виховання довільної поведінки дітей молодшого дошкільного віку у предметно-практичній діяльності - Пархомчук, Леся Леонідівна (My University, 2023)
Кваліфікаційну роботу присвячено аналізу довільності як здатності дитини молодшого дошкільного віку свідомо регулювати власну поведінку, підкоряти її певним правилам та досягати поставленої мети предметно-практичної діяльності. Розкрито зв’язок елементарних форм саморегуляції поведінки з особистісним зростанням дітей четвертого року життя. Визначено критерії оцінки рівнів сформованості в ранньому онтогенезі довільної поведінки й схарактеризовано показники кожного критерію. Теоретично обґрунтовано педагогічні умови ефективного формування у зростаючої особистості довільної поведінки, наголошено, що ключовим моментом оптимізації освітнього процесу у ЗДО виступає закладання основ становлення і розвитку суб’єктної позиції, створенну з цією метою розвивального середовища.
The qualification work is devoted to the analysis of arbitrariness as the ability of a child of younger preschool age to consciously regulate behavior, to obey certain rules and to achieve the set goal of subject-practical activity. The relationship between elementary forms of self-regulation of behavior and personal growth of children in the fourth year of life is revealed. The criteria for assessing the levels of formation in the early ontogenesis of voluntary behavior were determined and the indicators of each criterion were characterized. Pedagogical conditions for the effective formation of voluntary behavior in a growing personality are theoretically substantiated, it is emphasized that the key point in the optimization of the educational process in special education is the laying of the foundations for the formation and development of the subject position created for this purpose in the developmental environment. Key words: personality development, arbitrary behavior, self-regulation mechanism, new formation of consciousness and personality, indicators of arbitrariness assessment, conditions for optimizing the educational process.
Keywords: довільна поведінка; механізм саморегуляції; новоутворення свідомості і особистості; розвиток особистості